Safety of vancomycin-loaded cement spacers for treating gram-positive periprosthetic joint infections in two-stage resection arthroplasty among patients with renal insufficiency - Yu-Chih Lin; Chih-Hsiang Chang; Chih-Chien Hu; Yung-Chieh Liang; Pang-Hsin Hsieh; Sheng-Hsun Lee; Sheng-Hsuan Lin (BMC Musculoskeletal Disorders)
Abstract Background The standard treatment for periprosthetic joint infections (PJI) typically involves a two-stage resection arthroplasty using antibiotic-loaded bone cement (ALBC) spacers. This study hypothesizes that there is no significant correlation between antibiotic levels in blood and synovial fluid and the patient’s kidney function, and that the success rates of staged resection arthroplasty are comparable between groups, specifically targeting gram-positive bacterial infections. Methods This retrospective review included patients treated from 2017 to 2022 with two-stage arthroplasty using vancomycin-loaded ALBC spacers, selectively targeting gram-positive infections. Patients with non-gram-positive infections or those with allergies or treatments affecting serum antibiotic levels were excluded. The study assessed comorbidities, renal function, specifics of the spacers, and vancomycin concentrations in joint fluid and blood. Results Among 62 PJI cases analyzed (22 hips and 40 knees), 34 patients (54.8%) had renal insufficiency (RI), associated with significantly lower albumin (2.64 g/dL vs. 3.43 g/dL, p < 0.05) and estimated glomerular filtration rate (eGFR) (58.17 mL/min/1.73 m² vs. 121.74 mL/min/1.73 m², p < 0.05). No significant differences were found in comorbidities, antibiotic regimen, or the weight of the ALBC spacers between the groups (p > 0.05). Both groups exhibited high vancomycin levels in joint fluid, with peak blood vancomycin levels inversely correlated with eGFR (coefficient − 3.612, 95% CI -8.543 to -2.753, p < 0.001). RI patients displayed higher peak blood vancomycin levels (1.23–5.43 mg/L) but remained below toxicity thresholds. The infection-free interval, aseptic revision rates, and bacterial profiles specific to gram-positive species showed no significant differences between the groups. Conclusion Systemic absorption of vancomycin from ALBC spacers was evident in patients with RI and inversely correlated with eGFR, yet remained well below toxic thresholds across all patients. These findings suggest that the use of vancomycin-loaded ALBC spacers appears to be safe for managing gram-positive infections in patients with varying renal function. Additionally, renal insufficiency did not adversely affect the infection-free interval, aseptic revision rates, or bacterial diversity. Level of evidence III.